The wage structure and gap between public and private sectors: an empirical study in urban China. Issue 1 (31st December 2023) - Li, Mingming; Zhang, Fumei
Abstract: The idea that the wage gap (W.G.) between the public sector (P.U.S.) and private sectors (P.R.S.) has widened is a point of contention among scholars, but to date, there has been no systematic discussion of changes in the W.G. and their causes in China. This article combines data from China's Urban Household Survey (U.H.S.) for 2004, 2008 and 2013 to examine changes in between-sector W.G.s and identify the causal factors by wage decomposition methods. Using ordinary least squares and a Heckman sample selection model, this study finds that public-sector workers consistently earn more than private-sector workers and that the W.G. is expanding, especially in upstream industries where state-owned enterprises (S.O.E.s) have monopoly status. In addition, the Oaxaca–Blinder (O.B.) decomposition method is adopted to reveal that the characteristic effect is the main cause of the W.G. Further, the regression and decomposition of the recentered influence function show that the effect of characteristics and coefficient effects differ across wage quantiles. This article indicates that the intersectoral W.G. in China is widening mainly as a result of differences in labour endowments and provides evidence to support government decision-making.